FAKTOR–FAKTOR YANG MEMPENGARUHI PERILAKU TERHADAP PEMILIHAN MAKANAN/MINUMAN MELALUI APLIKASI ONLINE PADA MAHASISWA POLTEKKES KEMENKES BANDUNG (Jurnal Kesehatan Siliwangi, 2022)
Online food/beverage ordering applications have become a growing trend in society. People are no stranger to online food ordering applications with various conveniences and services that are an attraction. Orders can be made anywhere and anytime, without having to come to the seller's place. Ordering food/beverages online is very practical, easy, fast, and saves time, especially for consumers who don't have free time to go to a restaurant.However, in addition to the benefits of using an online food ordering application, if the food selection is not appropriate and the use of the application is done excessively, it will certainly affect the health of the body. This study aims to determine the factors that influence the behavior of food/beverage selection through online applications for students at the Health Polytechnic Bandung. The research design used a survey design cross-sectional and used a random sampling with a sample size of 188 students. This research was conducted from January 2021 to February 2021 by filling out online questionnaires using Google Forms. The results of this study indicate that most students who order food through online applications have poor behavior, namely as many as 101 students (53.7%), the level of knowledge is good, namely as many as 108 students (57.4%), and good attitudes, namely as many as 121 students (56.9%). It is hoped that students will be wiser in choosing food/beverages through online applications by applying the health knowledge that has been obtained while studying at the Health Polytechnic Bandung.